2020
DOI: 10.2147/ott.s228317
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tizanidine (Hydrochloride) Inhibits A549 Lung Cancer Cell Proliferation and Motility Through Regulating Nischarin</p>

Abstract: Purpose: Tizanidine hydrochloride (TZN) is a centrally acting α 2-adrenergic agonist. In this study, we aimed to explore the role of TZN on human lung cancer and to elucidate its underlying mechanisms. Methods: The effect of TZN treatment in A549 cell proliferation, migration, invasion and apoptosis was evaluated by CCK8, transwell and flow cytometer assays. The expression of apoptosis-related proteins and the activation of AKT and Wnt3a/β-catenin pathways were detected by Western blot. From the data of DrugBa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In ovarian cancer, promoter hypermethylation-induced NISCH silence-promoted cell cycle progression through the focal adhesion kinase (FAK) signal [22]. Besides, a previous study indicated that tizanidine hydrochloride inhibited A549 cell proliferation and mobility via upregulating the NISCH expression [24]. All the aforementioned results support the results of our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In ovarian cancer, promoter hypermethylation-induced NISCH silence-promoted cell cycle progression through the focal adhesion kinase (FAK) signal [22]. Besides, a previous study indicated that tizanidine hydrochloride inhibited A549 cell proliferation and mobility via upregulating the NISCH expression [24]. All the aforementioned results support the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…e expression of NISCH is closely related to tumorigenesis, progression, and poor prognosis in cancers, including breast, lungs, and ovarian cancers [22,24,37,38]. A series of publications reported that NISCH was a tumor-suppressive factor in breast cancer, and NISCH-expressing cells delivered exosomes that suppress breast cancer cell growth and mobility [21,37,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implications of involvement in regulation of cell movement and its potential as a druggable receptor made it an interesting target in cancer research. Over the past 20 years nischarin (NISCH) role has been studied mostly in the breast, ovarian [ 3 ] and lung cancer [ 4 , 5 ]. Seminal work on elucidating NISCH role in breast cancer initiation and progression has been done by the Alahari group [ 6 ].…”
Section: Introductionmentioning
confidence: 99%